Rethinking food-derived bioactive peptides for antimicrobial and immunomodulatory activities - Agyei, D.; Danquah, Michael (Pergamon Press, 2012)
Bioactive peptides from food proteins have been studied over the past decade to elucidate their biological potency in the major systems of the body such as the digestive, cardiovascular, nervous, and immune systems. Some bioactive peptides have been established for their antimicrobial roles as well as humoral and cell-mediated immune functions and thus have prospects of being incorporated as ingredients in functional foods, nutraceuticals and pharmaceuticals where their biological activities may assist in the control and prevention of diseases.However, further insightful research on the pharmacokinetics of immunomodulatory peptides invivo and clinical studies are needed to firmly establish their therapeutic potency.